Ternary semiconductor photocatalysts for the degradation of benzene-toluene-xylene in aqueous phase - Zul Adlan Mohd. Hir, 1988-; Rusmidah Ali; Wan Azelee Wan Abu Bakar; Fakulti Sains (2013)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2013